PENGARUH STRES KERJA TERHADAP TURNOVER INTENTION MELALUI MEDIASI KOMITMEN ORGANISASIONAL PADA RESTORAN QUEEN’S TANDOOR SEMINYAK - Pranata, Gede Dirga; Ketut Netra, I Gusti Salit (E-Jurnal Manajemen; Vol 8 No 6 (2019)DO - 10.24843/EJMUNUD.2019.v08.i06.p09, 2019)
The purpose of this study is to explain the effect of work stress on turnover intention through the mediation of organizational commitment. This research was conducted at the Queen’s Tandoor Seminyak restaurant in Badung Regency. The number of samples in this study were 79 employees, through the nonprobability sampling method, especially saturated samples. Data collection is done through distributing questionnaires, interviews, and observations. The analysis technique used is path analysis. Based on the results of the study found that work stress has a positive and significant effect on turnover intention. Job stress has a negative and significant effect on organizational commitment. Organizational commitment has a negative and significant effect on turnover intention. Organizational commitment can mediate the effect of work stress on turnover intention. Management should pay attention to the imposition of work so as not to exceed the ability of employees who can lead to job stress and increase employee involvement in the company. Keywords: work stress, organizational commitment, turnover intention